Attitudes Towards Aging, Depression, Physical Functioning, and Pain Among Women Living with HIV of Reproductive Age. - Cherenack, Emily M.; Brophy, Theodora F.; Max, Margarita Avila; Graubard-Silebi, Alicia; Nogueira, Nicholas F.; Pan, Yue; Westreich, Daniel; Topper, Elizabeth F.; Konkle-Parker, Deborah; Rana, Aadia; Kassaye, Seble G.; Sheth, Anandi N.; et al. (AIDS & Behavior, 2025)
Positive attitudes towards aging (ATA) are associated with better mental and physical health in the general population and with lower depressive symptoms among men living with HIV. Little is known about ATA among women of reproductive age living with HIV (WWH), who often experience premature aging, depression, and chronic pain. This study examined the association of ATA with HIV, physical functioning, and pain among women 19–45 years-of-age. From 2021 to 2022, survey data were collected at baseline from 143 WWH and 39 women without HIV (WWOH) across the southern United States; 94 WWH also completed a six-month follow-up visit. Baseline ATA was compared across HIV status. Among WWH, correlations between ATA, participant factors relevant in prior research (i.e., age, depression, illness), pain, and physical functioning were examined. Regressions examined the association of baseline ATA with physical functioning and pain across visits, including when controlling for potential confounders. Having one or more negative ATA was reported by an equal proportion of WWH (57%) and WWOH (58%). Among WWH, more positive ATA correlated with lower depressive symptoms, better physical functioning, and lower pain at baseline. Lower depressive symptoms correlated with better physical functioning and lower pain at baseline. In regressions, more positive ATA was associated with better physical functioning at baseline and follow-up. A weak association of ATA with pain at baseline was not significant at follow-up or after controlling for depression. Research is warranted to examine how combined interventions to improve ATA, depression, and pain can support well-being among reproductive-aged WWH.